2006
DOI: 10.1074/jbc.m512510200
|View full text |Cite
|
Sign up to set email alerts
|

Metal Ion Site Engineering Indicates a Global Toggle Switch Model for Seven-transmembrane Receptor Activation

Abstract: Much evidence indicates that, during activation of seven-transmembrane (7TM) receptors, the intracellular segments of the transmembrane helices (TMs) move apart with large amplitude, rigid body movements of especially TM-VI and TM-VII. In this study, AspIII:08 (Asp 113 ), the anchor point for monoamine binding in TM-III, was used as the starting point to engineer activating metal ion sites between the extracellular segments of the ␤ 2 -adrenergic receptor. Cu(II) and Zn(II) alone and in complex with aromatic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
86
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(92 citation statements)
references
References 55 publications
6
86
0
Order By: Relevance
“…For example, the monoamine receptors contain an Asp at position III:08/3.32 that interacts with the quaternary amine of the monoamine ligand (30, 38 -40). Also, III:08/3.32 constitutes a crucial part of activating bi-and tridentate metal ion binding sites engineered into the ␤ 2 -adrenergic receptor (27) and also serves as an anchor point for C5a binding to the C5a receptor (41) as well as for most chemokines and small molecule agonists targeting chemokine receptors (42). We also found that Phe-substitution of Thr 115 at position III:12/3.36 and Met 297 at VII:09/ 7.42 completely destroyed the GSK682753A-mediated inhibition, whereas Ala substitution did not (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the monoamine receptors contain an Asp at position III:08/3.32 that interacts with the quaternary amine of the monoamine ligand (30, 38 -40). Also, III:08/3.32 constitutes a crucial part of activating bi-and tridentate metal ion binding sites engineered into the ␤ 2 -adrenergic receptor (27) and also serves as an anchor point for C5a binding to the C5a receptor (41) as well as for most chemokines and small molecule agonists targeting chemokine receptors (42). We also found that Phe-substitution of Thr 115 at position III:12/3.36 and Met 297 at VII:09/ 7.42 completely destroyed the GSK682753A-mediated inhibition, whereas Ala substitution did not (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We initially focused on TM-III because it is known to be one of the key players in 7TM receptor activation, during which the top of this helix has been hypothesized to perform an inward see-saw movement, as described in the global toggle switch model (27)(28)(29). Specifically, position III:08/3.32 in TM-III has been shown to be important for ligand binding and helical movement as seen in, for example, the ␤-adrenergic subfamily (30).…”
Section: The Expression Level Of Ebi2 Modulates Antibody-induced B Cementioning
confidence: 99%
“…Multiple active states have been assumed on the basis of theoretical and modeling considerations (Kenakin, 1995;Leff et al, 1997; FRET TECHNIQUES FOR GPCR ACTIVATION AND SIGNALING Buranda et al, 2007;Onaran and Costa, 2009;Kenakin and Miller, 2010) and because of ligand-specific "biased" effects of various agonist/receptor systems (Violin and Lefkowitz, 2007;Drake et al, 2008;Shukla et al, 2008;Rajagopal et al, 2011). Metal chelating strategies, originally developed to prevent the activation of GPCRs (Sheikh et al, 1996;Elling et al, 1999Elling et al, , 2006, revealed for the PTH receptor that different conformations were involved in coupling to G-proteins versus ␤-arrestins (Vilardaga et al, 2001); furthermore, the determinants of this receptor for ␤-arrestin binding and internalization were shown to be different (Vilardaga et al, 2002). Similar distinctions between requirements for activation and endocytosis were seen for the complement 5a receptor (Whistler et al, 2002).…”
Section: B Receptor Conformational Changes In Intact Cellsmentioning
confidence: 99%
“…The change of the toggle switch, depending on cis/trans isomerisation, may produce a domino effect, i.e. a maximization of the proline-induced kink in TM6 to facilitate helices movements, a breakage of the "ionic lock", a rearrangement of cytoplasmic loops and helices, leading to an "open" cytoplasmic surface [71,72,73,169,170]. Moreover, the residue (Trp-265) may also act as a gatekeeper which is able to mediate the signal transfer from the extracellular region to the cytoplasmic surface for coupling to the G protein.…”
Section: Sequential Activation Process Of Rhodopsinmentioning
confidence: 99%